2011
DOI: 10.1074/jbc.m111.219576
|View full text |Cite
|
Sign up to set email alerts
|

Queuosine Deficiency in Eukaryotes Compromises Tyrosine Production through Increased Tetrahydrobiopterin Oxidation

Abstract: Queuosine is a modified pyrrolopyrimidine nucleoside found in the anticodon loop of transfer RNA acceptors for the amino acids tyrosine, asparagine, aspartic acid, and histidine. Because it is exclusively synthesized by bacteria, higher eukaryotes must salvage queuosine or its nucleobase queuine from food and the gut microflora. Previously, animals made deficient in queuine died within 18 days of withdrawing tyrosine, a nonessential amino acid, from the diet (Marks, T., and Farkas, W. R. (1997) Biochem. Biophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
76
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 53 publications
(57 reference statements)
0
76
0
Order By: Relevance
“…PreQ 1 and Q biosynthesis genes are required for effective nitrogen-fixing symbiosis between Sinorhizobium meliloti and the barrel clover plant (Marchetti et al, 2013). Also, glutamyl-Q, another Q derivative, has been linked to effective stress response in S. flexneri (Caballero et al, 2012), while Q-deficiency halts tyrosine production in germ-free mice (Rakovich et al, 2011). In human and murine cancer cells, lack of Q-modification in tRNAs has been associated with cell proliferation, anaerobic metabolism, and malignancy (Elliot et al, 1984; Pathak et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PreQ 1 and Q biosynthesis genes are required for effective nitrogen-fixing symbiosis between Sinorhizobium meliloti and the barrel clover plant (Marchetti et al, 2013). Also, glutamyl-Q, another Q derivative, has been linked to effective stress response in S. flexneri (Caballero et al, 2012), while Q-deficiency halts tyrosine production in germ-free mice (Rakovich et al, 2011). In human and murine cancer cells, lack of Q-modification in tRNAs has been associated with cell proliferation, anaerobic metabolism, and malignancy (Elliot et al, 1984; Pathak et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…PreQ 1 is a guanine-derived nucleobase ( Figure 1A ) that is known to be incorporated in the wobble position of tRNAs containing the GUN anticodon sequence and then further modified to yield queuosine (Q) (Iwata-Reuyl, 2008). The presence of Q in tRNAs improves their ability to read degenerate codons (Meier et al, 1985), while the absence of enzymes involved in Q biosynthesis or salvage results in deleterious phenotypes in a wide array of organisms (Durand et al, 2000; Rakovich et al, 2011). Despite the near-ubiquitous presence of preQ 1 in organisms (Iwata-Reuyl, 2008), much remains unknown regarding the function of this modified nucleobase and its derivatives in cells.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study demonstrated that liver extracts from mice that lack the enzymes for incorporating Q into RNA contained decreased levels of tetrahydrobiopterin, the cofactor required for the conversion of phenylalanine to tyrosine by phenylalanine hydroxylase [31]. …”
Section: Biological Distribution Of 7-deazapurine Metabolitesmentioning
confidence: 99%
“…Altered levels of tRNA modification have been linked to several disorders including cancers (2)(3)(4)(5)(6)(7)(8). One of the most common modified nucleosides, dihydrouridine, is produced by reduction of the C5-C6 double bond in uridine.…”
mentioning
confidence: 99%